2018
DOI: 10.3390/brainsci8120225
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Motor Cortical Representation of Muscles Following Incomplete Spinal Cord Injury in Humans

Abstract: (1) Background: The primary motor cortex (M1) experiences reorganization following spinal cord injury (SCI). However, there is a paucity of research comparing bilateral M1 organization in SCI and questions remain to be answered. We explored the presence of somatotopy within the M1 representation of arm muscles, and determined whether anatomical shifts in these representations occur, and investigated the symmetry in organization between the two hemispheres.; (2) Methods: Transcranial magnetic stimulation (TMS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…These studies demonstrated that the representations of less impaired muscles shift and expand following a complete or incomplete SCI, whereas representations of more impaired muscles retract or are absent. 14,7175 However, our fMRI results showed that SCI patients had a similar level of finger-related movement activity in M1 as controls, and preserved somatotopic hand representations in S1. It is possible that reorganisation and preservation of the original function could co-occur within cortical areas.…”
Section: Discussionmentioning
confidence: 59%
“…These studies demonstrated that the representations of less impaired muscles shift and expand following a complete or incomplete SCI, whereas representations of more impaired muscles retract or are absent. 14,7175 However, our fMRI results showed that SCI patients had a similar level of finger-related movement activity in M1 as controls, and preserved somatotopic hand representations in S1. It is possible that reorganisation and preservation of the original function could co-occur within cortical areas.…”
Section: Discussionmentioning
confidence: 59%
“…TMS studies similarly induce current in localised areas of M1 to induce a peripheral muscle response of cortically neighbouring body parts. These studies demonstrated that the representations of less impaired muscles shift and expand following a complete or incomplete SCI ( Fassett et al, 2018 ; Freund et al, 2011a ; Levy et al, 1990 ; Streletz et al, 1995 ; Topka et al, 1991 ; Urbin et al, 2019 ). Our fMRI results showed that tetraplegic patients had a preserved somatotopic hand representation in S1, though this deteriorated over time.…”
Section: Discussionmentioning
confidence: 92%
“…Transcranial magnetic stimulation (TMS) studies induced current in localised areas of SCI patients’ primary motor cortex (M1) to induce a peripheral muscle response. They found that representations of more impaired muscles retract or are absent while representations of less impaired muscles shift and expand ( Fassett et al, 2018 ; Freund et al, 2011a ; Levy et al, 1990 ; Streletz et al, 1995 ; Topka et al, 1991 ; Urbin et al, 2019 ). Similarly, human fMRI studies have shown that cortically neighbouring body part representations can shift towards, though do not invade, the deprived M1 and S1 cortex ( Freund et al, 2011b ; Henderson et al, 2011 ; Jutzeler et al, 2015 ; Wrigley et al, 2018 ; Wrigley et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…SCI largely damages both sides of the spinal cord resulting in asymmetrical deficits in sensory and motor function 54 , 74 . Thus, the handedness of SCI participants is affected by the injury 76 . Thirteen SCI subjects were right-handed before the injury and this arm corresponded to the “more affected arm” after the injury.…”
Section: Methodsmentioning
confidence: 99%